Evolution of the Alpine orogenic belts in the Western Mediterranean region as resolved by the kinematics of the Europe-Africa diffuse plate boundary - (:unkn) unknown (My University, 2021)
This research has been supported by the Centre National de la Recherche Scientifique (CNRS-INSU), the French Geological Survey (BRGM), and Total through theOROGEN project, as a post-doctoral grant to Paul Angrand. We acknowledge the members of the OROGEN scientific project for support and discussions during the postdoc of Paul Angrand, in particular leaders and PIs Emmanuel Masini, Sylvain Calassou, Olivier Vidal, Isabelle Thinon, Laure Moen-Maurel, Mary Ford, Laurent Jolivet, Gianreto Manatschal, as well as former postdocs and phds Gianluca Frasca, Adrien Romagny, Riccardo Asti, and Nicolas Saspiturry. Emmanuel Masini is particularly thanked for continuous discussions during the postdoc of Paul Angrand, which greatly contributed to the development and maturation of this project. Oscar Fernandez is acknowledged for discussions about the evolution of Iberia in the frame of the Atlantic opening. We thank Editor Olivier Lacombe for his patience during the submission of this manuscript. We thank reviewers Antonio Schettino, Reinoud Wissers, and Charlotte Nielsen for their constructive and helpful comments about our (large) manuscript. Associate Editor David Pedreira is thanked for pointing out mistakes about the Basque-Cantabrian Basin in an earlierversion of the manuscript .
Keywords: African Research